2000
DOI: 10.1046/j.1365-2818.2000.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Charge effect in point projection images of carbon fibres

Abstract: Nanometre‐sized carbon fibres across holes have been observed in a lensless point projection field‐emission microscope operating between 100 and 300 eV. At sufficiently high magnification fringe patterns appear; with the help of simulations we show that they are strongly dependent on the charge density of the fibres. These patterns are characterized by an odd number of fringes with a central fringe that becomes very bright as the charge increases. Average diameter and linear charge density have been obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…At large tip-object distances, the patterns of the first group looked rather similar to the Fresnel fringes generated by a narrow strip, simulated by Prigent et al, 13 as shown in Figure 7(a). The tip approach changed the Fresnel-like fringe patterns into fringes of equal spacing, as shown in Figure 7(b), indicating that the MWCNT began to function as an electron biprism at small tip-object distances.…”
Section: Resultssupporting
confidence: 75%
“…At large tip-object distances, the patterns of the first group looked rather similar to the Fresnel fringes generated by a narrow strip, simulated by Prigent et al, 13 as shown in Figure 7(a). The tip approach changed the Fresnel-like fringe patterns into fringes of equal spacing, as shown in Figure 7(b), indicating that the MWCNT began to function as an electron biprism at small tip-object distances.…”
Section: Resultssupporting
confidence: 75%
“…Figure 1) and leads to a constricted (or widened) projection image. In LEEPS images of carbon fibers and nickel nanowires, a positive object charging was found 19, 20…”
mentioning
confidence: 99%
“…At high magnification the image is dominated by interference and must be treated as an in‐line hologram 16–18. LEEPS has been used for the imaging of nanoscale objects, such as single‐polymer fibers, DNA, carbon nanotubes, and metal NWs 6, 15, 19–21. Due to the low electron energy, the LEEPS image is very sensitive to electric fields surrounding the object.…”
mentioning
confidence: 99%
“…Since then, several groups explored its experimental and theoretical foundations. Experimental imaging has been performed with carbon fibers [7,8], carbon nanotubes [9][10][11][12], and thin metal wires [13]. Holographic imaging of single polymer fibers [14] and of unstained individual DNA molecules [15,16] was also reported.…”
mentioning
confidence: 99%
“…In the case of electrostatic charging it was shown that the corresponding image distortions are correctable by an appropriate reconstruction scheme [11,24,25]. The alteration of LEEPS images by electrostatic charges might be used to map linear charge distributions along nanowires or nanotubes as shown by Dorozhkin and Dong [26].…”
mentioning
confidence: 99%